(untitled) (Journal of the College of Basic Education, 2023)
Praise be to God, who erases slips and pardons, forgives errors and allows. Everyone who takes refuge in it is successful. The one who works for him is profitable, I praise him for the evening and the morning, and I bear witness that there is no god but God, the rich, the generous, the one who gives The broad and the broader, and I bear witness that Muhammad is His servant and His Messenger who sacrificed himself and his wealth to God and explained the truth and made it clear. May Allah’s blessings and peace be upon him and his family, and after that. Zakat is the third pillar of the Islamic religion, which is the basis on which the human beings and live in